Birds Challenges and Opportunities for Business, Conservation and Research - Mikkola, Heimo (IntechOpen, 2021)
For many humans, birds are the most fascinating group of animals and they are definitely among the best-known and studied organisms. Thanks to global citizen science data, we know that there are some 50 billion individual birds in the world at present, which is about six birds for every human on the planet. Birds have an important role as indicators of the state of the environment, giving them high public value. Human-related global impacts such as climate changes and accelerating urbanization force extant species to continuous adaptations, population modifications, or even outright extinction. This book includes nine chapters covering such topics as bird genetics, the colour of avian plumage, conservation problems, sustainable hunting, habitat disturbance, range expansion and introductions, and long-term bird population changes and challenges. A key chapter explains the genetic rules and reasons why we have continuously more bird species in the world and why we may end up having 7,000 species more than the present 11,000 species.